1999
DOI: 10.1021/jm980701v
|View full text |Cite
|
Sign up to set email alerts
|

CoMFA Study of Novel Phenyl Ring-Substituted 3α-(Diphenylmethoxy)tropane Analogues at the Dopamine Transporter

Abstract: A series of phenyl ring-substituted analogues of 3alpha-(diphenylmethoxy)tropane (benztropine) has been prepared as novel probes for the dopamine transporter. Cross-validated comparative molecular field analysis (CoMFA) models of the binding domain on the dopamine transporter were constructed using 37 geometry-optimized structures of these compounds and their corresponding binding affinities (K(i) values) for the displacement of [(3)H]WIN 35,428 or potency of [(3)H]dopamine uptake inhibition (IC(50) values) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 33 publications
4
37
0
Order By: Relevance
“…36 This study further confirmed structure-activity relationships, but also demonstrated that the steric interaction of these compounds was the most prominent component to predict DAT binding affinities. 36 These studies also provided early support for the differences in structure-activity relationships between these tropane-based dopamine uptake inhibitors and the 3-aryl tropane or cocaine series of compounds.…”
Section: Structure-activity Relationships At Datsupporting
confidence: 69%
See 2 more Smart Citations
“…36 This study further confirmed structure-activity relationships, but also demonstrated that the steric interaction of these compounds was the most prominent component to predict DAT binding affinities. 36 These studies also provided early support for the differences in structure-activity relationships between these tropane-based dopamine uptake inhibitors and the 3-aryl tropane or cocaine series of compounds.…”
Section: Structure-activity Relationships At Datsupporting
confidence: 69%
“…CoMFA studies have been conducted on the 3-position of the tropane ring for both the cocaine and 3-aryl tropane class of compounds 82,83,87 and the benztropines. 36 The 3D-QSAR studies lend further support for distinctive structure-activity relationships at this position and differing binding interactions at the DAT between these two classes of compounds. CoMFA studies performed on cocaine and the 3-aryl tropane analogues suggested that the steric component is a predominant factor in their binding affinities, with electrostatics playing a smaller, yet significant role.…”
Section: B Cocaine and The 3-aryl Tropanesmentioning
confidence: 73%
See 1 more Smart Citation
“…To test this hypothesis, we have used a library of 3-phenyltropane analogs and substituted amphetamines to examine structural components of these compounds that are critical for recognition by hSERT, dSERT, and the H The results of these assays were used as input for modeling using CoMFA. CoMFA has proven valuable in previous studies as a method to model protein-ligand interactions in systems that lack protein crystal structures or other definitive structural information (Carroll et al, 1994;Wilcox et al, 1998;Li et al, 1999;Newman et al, 1999). The six models presented here indicate differences in recognition on four levels.…”
mentioning
confidence: 91%
“…25 The histamine H 1 -pharmacophore was then used for superimposition of the BZT analogs. The quality of the superimpositions was evaluated based on the RMSD values and the ΔVs as defined earlier.…”
Section: Molecular Modelingmentioning
confidence: 99%